ANALISIS PENYELENGGARAAN PEMERINTAHAN DI KECAMATAN TANETE RIATTANG TIMUR KABUPATEN BONE - M Arsyad Maf'ul; Sri Agustina; Bakhtiar Bakhtiar (SUPREMASI: Jurnal Pemikiran, Penelitian Ilmu-ilmu Sosial, Hukum dan Pengajarannya, 2017)
This study aims to investigate the implementation of governance in the Eastern District of Tanete Riattang Bone regency in community service and the factors that affect public services in the district of East Riattang Tanete Bone regency. Researchers used data collection techniques through observation, interviews and documentation. Data have been obtained from the results of the study were processed using qualitative analysis to examine the implementation of governance in the sub Tanete Riattang eastern districts bone and the factors that influence it. The results showed that: 1) Implementation of the government in the district penyelenggaraa Tanete Riattang east district bone in community service that focuses on the timeliness of service, courtesy and hospitality in providing services, access to services, convenience in obtaining services. In timeliness of services there is still a delay but still more often on time. Kesopana and hospitality in providing services has been undone by a well. At the district office is also already provide convenience to the people who want to do service by providing free services, free of charge. Only the creator of comfort in the office facility is still minimal, due to the less spacious office buildings and the lack of infrastructure. 2) Factors Influencing Government Conduct in the Public Service in the District Tanete East Riattang namely: a) Supporting factors governance in public service in the District Tanete East Riattang consisting of (1) Leadership Head, (2) the Work Environment. b) Factors inhibiting the public service delivery is poor facilities and infrastructure sub-district.